Features of nutrition of women and children in Ishim district of Omsk region during the Great Patriotic War - A. A. Frolova (Омский научный вестник: Серия "Общество. История. Современность")
The article reveals the features of catering in the Ishim district of the Omsk region during the Great Patriotic War. The author considers the issue of supplying the inhabitants of the home front with food products, as well as models of women’s way out of the situation of the food crisis. The source base on this topic includes the materials of the Ishim archive, as well as materials of oral history in the form of memoirs of contemporaries. Among the office documentation stored in the Ishim archive, reports and minutes of meetings of the City Council of People’s Deputies, which reflect the official level of perception of everyday problems, are of particular interest. Sources of personal origin provide an opportunity to more deeply understand events at the individual level. The periodical press presented by the local newspaper «Hammer and Sickle» helps to reconstruct the picture of everyday life of the Ishim people during the Great Patriotic War. Despite the subjectivity of the sources, based on the memories of the participants in the events, one can draw up a single picture of everyday life, identify the features of this period. The author uses a historical-everyday approach, a historical-anthropological approach. As part of the study, methods of oral history are used. The author comes to the conclusion that the everyday life of citizens during the Great Patriotic War has been insufficiently studied. The article focuses on catering in the city of Ishim, and also shows the models of the population’s way out of the food crisis situation. In addition, the article reveals the issue of the influence of the natural-geographical factor on the daily life of the population of the Ishim region.